Poole’s Stochastic IS-LM Model and Optimal Monetary Policy Rule: A Framework for Graduate Teaching - Amaresh Das (Journal of Education and Vocational Research, 2012)
Our comment revisits Poole’s popular exposition of the IS-LM model and proceeds to extend the discussion to best derive the optimal monetary policy rule. The key assumption is that the economy is closed with no transactions in goods and capital. This will help us better understand the basic working of the macro economy.